N-Acetylcysteine Reverses Antiretroviral-Mediated Microglial Activation by Attenuating Autophagy-Lysosomal Dysfunction - Tripathi, Ashutosh; Thangaraj, Annadurai; Chivero, Ernest T.; Periyasamy, Palsamy; Burkovetskaya, Maria E.; Niu, Fang; Guo, Ming-Lei; Buch, Shilpa (Frontiers in Neurology, 2020)
Successful suppression of viral replication by combined antiretroviral therapy (cART) in HIV-1 infected individuals is paradoxically also accompanied by an increased prevalence of HIV-associated neurocognitive disorders (HAND) in these individuals. HAND is characterized by a state of chronic oxidative stress and inflammation. Microglia are extremely sensitive to a plethora of stimuli, including viral proteins and cART. The current study aimed to assess the effects of cART-mediated oxidative stress on the induction of inflammatory responses in microglia. In the present study, we chose a combination of three commonly used antiretroviral drugs - tenofovir disoproxil fumarate (TDF), emtricitabine (FTC) and dolutegravir (DTG). We demonstrated that exposure of microglia to the chosen cART cocktail induced generation of reactive oxygen species (ROS), subsequently leading to lysosomal dysfunction and dysregulated autophagy, ultimately resulting in the activation of microglia. Intriguingly, the potent antioxidant, N-acetylcysteine (NAC), reversed the damaging effects of cART. These in vitro findings were further corroborated in vivo wherein cART-treated HIV transgenic (Tg) rats demonstrated increased microglial activation, exaggerated lysosome impairment and dysregulated autophagy in the prefrontal cortices compared to HIV Tg rats not exposed to cART. Similar to in vitro findings, treatment of HIV Tg rats with NAC also mitigated the deleterious effects of cART. Taken together, our findings suggest that oxidative stress-mediated lysosomal dysfunction plays a critical role in the pathogenesis of HAND in drug treated HIV-infected individuals and that, antioxidant-mediated mitigation of oxidative stress could thus be considered as an adjunctive therapeutic strategy for ameliorating/dampening some of the neurological complications of HAND.